Extraction treatment using a palatal implant for anchorage - Giancotti Aldo; Greco Mario; Docimo Raffaella; Arcuri Claudio (Sciendo, 2003)
Aim: To describe the use of Straumann Orthosystem implants for orthodontic anchorage.